Biotemplated hierarchical porous-structure of ZnAl-LDH/ZnCo2O4 composites with enhanced adsorption and photocatalytic performance. Issue 16 (1st February 2016) - Yu, Jing; Lu, Lu; Li, Jia; Song, Peng
Abstract : Schematic illustration of the synthesis of pollen-like ZnAl-LDH/ZnCo2 O4 and its derived metal oxides. Abstract : Hierarchically porous ZnAl-LDH/ZnCo2 O4 composites were synthesized by pine pollen via a two-step process involving self-assembly of ZnCo2 O4 nanoparticles and hydrothermal synthesis of zinc aluminum layered double hydroxide with CO3 2− as interlayer anion (abbreviated as ZnAl-LDH). The characteristics of the obtained samples were investigated by XRD, SEM, EDS, TEM, FTIR, BET and DRS. These results demonstrated that the synthesized ZnAl-LDH/ZnCo2 O4 and its derived metal oxides all retained the structure of pine pollen grains. Layered ZnAl-LDH was dispersed uniformly on the surface of a support of ZnCo2 O4 ellipsoids. The adsorption of Congo red (CR) onto the as-synthesized samples was systematically investigated. The kinetic studies suggested that the adsorption process followed a pseudo-second-order kinetic model. In addition, the catalytic activities of the obtained samples for CR degradation under simulative sunlight irradiation were also evaluated. It was found that the derived metal oxides exhibited better catalytic activity for CR degradation than ZnAl-LDH/ZnCo2 O4 and the degrading efficiency of CR was about 91%.